PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN MARTABAK ITANG DI PAKOWA MANADO - Peggy Nurhayati Suleman; Leonardus R. Rengkung; Juliana R. Mandei (Sam Ratulangi University, 2018)
This study aimed to determine the consumer behavior based on individual, environmental, and marketing strategy factors in the buying decision of Martabak Itang in Pakowa, Manado. This study was expected to be the source of information to entrepreneurs about the consumers behavior in buying Martabak Itang in Pakowa, Manado, so that companies can determine and improve the strategy in dealing with the competition.The data used in this study were primary data and secondary data. The sampling method in this study was Accidental Sampling, which was taking the sample that accidentally met with the researcher. The total of sample taken in this study was 60 people. The sampling process was conducted in 6 days, which was the number of samples taken was 10 buyers for day for a week, from Monday until Saturday. The result of this study showed that individual factors measured by need and motivation did not affect the buying decision. Environmental factors measured by family and friends influencethe buying decision. While marketing strategy factors measured by product, price, promotion, location, and service influencethe buying decision.*lrr*.